Strengthening additively manufactured Inconel 718 through in-situ formation of nanocarbides and silicides - Tekoğlu, Emre; O’Brien, Alexander D.; Liu, Jian; Wang, Baoming; Kavak, Sina; Zhang, Yong; Kim, So Yeon; Wang, Shitong; Ağaoğulları, Duygu; Chen, Wen; Hart, A. John; Li, Ju (Elsevier BV, 2023)
We report additive manufacturing (AM) of a nickel superalloy metallic matrix composite (Ni-MMC) using laser powder bed fusion (LPBF). Nanoceramic-containing composite powders were prepared by high-speed blender declustering and ball milling of as-received SiC nanowires (2 vol%) and Inconel 718 alloy powders, which produced a homogeneous decoration of SiC on the surfaces of Inconel particles. Analysis of the as-printed specimens revealed the dissolution of SiC nanowires during laser melting, leading to the in-situ formation of Nb- and Ti-based silicide and carbide nanoparticles. These in-situ formed nanoparticles resulted in a more desirable solidification microstructure of the AM Inconel 718 with fewer printing defects (cracks and pores) and slightly refined grain sizes. Mechanical characterization of the as-printed Ni-MMCs revealed notable increases in hardness, yield strength (by 16%), and ultimate tensile strength (sigma(UTS), by 12%) compared to the reference samples without SiC addition. After heat treatment, the same composite samples displayed a 10% higher sUTS compared to identically treated unreinforced material while maintaining similar to 14% total tensile elongation. We believe this in-situ precipitate formation presents a simple and effective method for strengthening additively manufactured high-temperature materials that could be used in the increasingly harsh environments in energy and propulsion applications.